THE STUDY OF NUTRITIONAL VALUE FROM GRESIK TRADITIONAL FOOD PRODUCTS - Yunita Siti Mardhiyyah (AGROINTEK, 2019)
Gresik is well known as one of the Islamic based tourism towns in East Java. This Islamic tourism encourages the development of typical souvenirs business in Gresik especially in food sector. Some Gresik traditional food are often used as souvenirs, such as pudak, jubung, and ayas. High sale promotes product innovation, especially in terms of taste creations, preservation / shelf life, as well as packaging. Unfortunately, these product innovation have not been supported with information related to product nutritional value. The nutritional value is important, considering the usage of information in food labelling as well as for the materials, process and packaging basic innovation. The study of Gresik traditional food nutritional value products consists of two stages, they were field-related observation and laboratory testing. Field observations were done to obtain information on raw materials and production processes from pudak, jubung and ayas. As for the test of nutritional value was done by proximate test. The results showed that pudak has moisture content (55.6%) twice higher than jubung and ayas (25.0% and 22.7%, respectively). All three products have a low fat content, which was below 1.0 g per serving. The protein content is also relatively low, i.e. only 2.1-2.8%. All three of these products are carbohydrate sources with the amount of 40.8-73.4% which gives a caloric amount of 120-185 kcal per serving. Implementation of nutritional information in food label could also give added value to the product.